2012
DOI: 10.1128/jvi.05452-11
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Glycine 33 Residue in Flexible Domain I of Hepatitis C Virus Core Protein Is Critical for Virus Infectivity

Abstract: Hepatitis C virus core protein forms the viral nucleocapsid and plays a critical role in the formation of infectious particles. In this study, we demonstrate that the highly conserved residue G33, located within domain 1 of the core protein, is important for the production of cell culture-infectious virus (HCVcc). Alanine substitution at this position in the JFH1 genome did not alter viral RNA replication but reduced infectivity by ϳ2 logs. Virus production by this core mutant could be rescued by compensatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 46 publications
4
22
0
Order By: Relevance
“…In agreement with previous observation, the amino acid metabolism in patients with hepatitis B virus (HBV) infection is significantly changed [46]. Conserved glycine 33 residue in flexible domain I of HCV core protein is critical for its virulent activity [47]. A previous study has demonstrated that HBV E-antigen physically associates with receptor interaction serine/threonine protein kinase 2 [48].…”
Section: Discussionsupporting
confidence: 85%
“…In agreement with previous observation, the amino acid metabolism in patients with hepatitis B virus (HBV) infection is significantly changed [46]. Conserved glycine 33 residue in flexible domain I of HCV core protein is critical for its virulent activity [47]. A previous study has demonstrated that HBV E-antigen physically associates with receptor interaction serine/threonine protein kinase 2 [48].…”
Section: Discussionsupporting
confidence: 85%
“…However, in the absence of structural data, we cannot exclude the possibility that mutations of other, also non-basic, residues in the same region will have an impact on core-NS5A interactions. Especially, if we take into consideration how important is for virus infectivity to maintain a close contact between two distant amino acids in HCV core as it has been demonstrated for residues G33 and F24 [75]. Next, we confirmed that core interacts with NS5A through the four N-terminal basic amino acids in cells expressing full-length HCV genome.…”
Section: Discussionsupporting
confidence: 68%
“…The plasmid pJFH1, containing the full‐length genomic cDNA sequence of the HCV genotype 2a strain and the N17/JFH1 plasmid were linearized using XbaI enzyme (New England Biolabs) and then treated with Mung Bean Nuclease (NEB) prior purification. Linearized plasmids were used as a template to generate in vitro transcribed RNA using MEGAscript T7 (Life Technologies, Milan, Italy).…”
Section: Methodsmentioning
confidence: 99%